Menyusun Strategi Mengelola Pendidikan: Antara Sebab dan Akibat - Ahmad, Nuril (MADINAH, 2016)
The passage of this Law of Nature article reads as follows: "All events are created by cause or if it is reversed: events are merely an effect." Until this understanding no one finds it difficult to understand. But when it is associated with ourselves and the reality of life we ​​receive, then it becomes a problem in itself. It is said that Mark Victor Hansen, author of Chicken Soap for the Soul series of books, should be asking the question between "are you the cause or the effect?" a total of 287 (two hundred and eighty seven) times to ensure a choice after a total business bankruptcy that forced him to live a vagrancy. He finally chose that all life events (reality) are 'effects' and he is the cause. Because Mark believes that there are still many individuals who think otherwise, then he pours his thoughts in the book mentioned above. Mark's work has been a best seller and led him to receive the Horatio Alger Award trophy.